Screening in colorectal cancer (CRC) - Stec, Rafał (Contemporary Oncology/Współczesna Onkologia, 2006)
Colorectal cancer (CRC) is one of major health problems in Poland. Every year about 11 000 new cases of CRC (EU about 220 000) are diagnosed; the number of deaths approaches 8 000 (EU 112 000). Five-year free disease survival rate does not exceed 20%. About 70% invasive cancer arises from adenomatous polyps. Early endoscopic diagnosis may reduce the risk of CRC more than 50% in the following 10 years. The prevalence of CRC increases after the age of 50. 50-70% tumors are located in the sigmoid colon and rectum. The ideal screening test is characterized by: adequate sensitivity and specificity, it should be cheap, simple and easy of approach. Some tests are available to screen subjects without risk for CRC: faecal occult blood test (FOBT), “ per rectum ” examination, flexible sigmoidoscopy (FS), combined FOBT and FS, optical colonoscopy, virtual colonoscopy, magnetic resonance colonography, double contrast barium enema (DCBE) and marker CEA (carcinoembryonic antigen). The discussion of screening tests regarding CRC is still open. Which screening test is the best in Poland? Every screening test has advantages and disadvantages. It seems that optimum screening in CRC in Poland is annual faecal occult blood test and per rectum examination after the age of 50.